Differential patterns of regional cerebral hypometabolism according to the level of cerebral amyloid deposition in patients with amnestic mild cognitive impairment. (6th October 2016) - Jeon, So Yeon; Yi, Dahyun; Byun, Min Soo; Choi, Hyo Jung; Kim, Hyun Jung; Lee, Jun Ho; Baek, Hyewon; Choe, Young Min; Lee, Younghwa; Woo, Jong Inn; Lee, Dong Young
Highlights: Different rCMglu pattern in aMCI according to cerebral amyloid deposition is shown. AMCI group has different neurodegeneration patterns according to amyloid level. Amyloid negative aMCI group might include non-AD neurodegenerative condition. Abstract: Although amnestic mild cognitive impairment (aMCI) with high cerebral deposition of amyloid-beta proteins (Aβ) could be classified as a prodromal state of Alzheimer's disease (AD) dementia, aMCI with the absence of or very little cerebral Aβ deposition is likely related to other pathophysiological processes. Thus, the present study aimed to investigate the differential patterns of regional cerebral glucose metabolism (rCMglu) according to the level of Aβ burden in the brains of patients with aMCI. This study included 25 patients with aMCI and 33 cognitively normal (CN) elderly individuals who underwent a comprehensive clinical examination, 11 C-labelled Pittsburgh Compound B (PiB) positron emission tomography (PET) scans, and 18 F-fluorodeoxyglucose (FDG) PET scans. Based on cerebral PiB retention, the aMCI subjects were divided into low Aβ (aMCI−, n = 10) and high Aβ (aMCI+, n = 15) subgroups, and differences in rCMglu among the CN group and aMCI subgroups were estimated on a voxel-by-voxel basis. Compared with the CN group, rCMglu was decreased in the bilateral medial temporal regions of the aMCI− subgroup and in the medial temporal cortices as well as the right precuneus of the aMCI+ subgroup. Additionally, rCMglu was lower in the right precuneus of the aMCI+ subgroup compared with the aMCI− subgroup. The present findings indicate that, even though both aMCI subgroups were phenomenologically very similar, the patients with aMCI− exhibited a markedly different regional pattern of functional neurodegeneration compared with the aMCI+ patients.